2020
DOI: 10.3390/ijerph17093325
|View full text |Cite
|
Sign up to set email alerts
|

Dentistry during the COVID-19 Epidemic: An Italian Workflow for the Management of Dental Practice

Abstract: The COVID-19 outbreak has raised concerns about infection control all over the world.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
58

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(125 citation statements)
references
References 33 publications
1
54
0
58
Order By: Relevance
“…Prosthetic, periodontal and all other planned procedures are recommended to be postponed until the end of the acute phase of the epidemic [ 56 ]. Until then, only emergency patients should be admitted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prosthetic, periodontal and all other planned procedures are recommended to be postponed until the end of the acute phase of the epidemic [ 56 ]. Until then, only emergency patients should be admitted.…”
Section: Resultsmentioning
confidence: 99%
“…It is recommended that prosthetic procedure be postponed until the end of the acute phase of the epidemic [ 56 ]. If it is necessary to restore missing teeth with permanent dentures, in patients with congenital hemorrhagic diathesis, supragingival crowns should be considered [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo a ADA, os serviços de emergência odontológica são sangramentos não controlados, celulite ou infecções bacterianas com comprometimento da via aérea, e traumatismo envolvendo os ossos da face, e os serviços de urgência compreendem dor dentária grave por inflamação pulpar, pericoronarite, osteíte pósoperatória cirúrgica, alveolite pós-operatória, abscessos ou infecção bacteriana localizada, fratura de dente, trauma dentário com avulsão ou luxação, cimentação final da coroa ou ponte se a restauração temporária for perdida, quebrada ou causando irritação na gengiva, biópsia de tecido anormal e tratamento dentário antes de procedimentos médicos críticos 15 .…”
Section: Resultados O Impacto Da Covid-19 Na Cavidade Bucalunclassified
“…Given the mode of transmission of COVID-19, dental healthcare professionals including dentists, dental assistants and dental hygienists are at high risk of exposure among all healthcare personnel [ 4 , 5 ]. In this regard, studies from multiple groups around the globe have reported on critical infection control measures [ 5 , 6 , 7 ] and guidelines for modifications to dental clinic workflows that were implemented during the pandemic [ 8 , 9 ]. Reports have also described the impact of COVID-19 on the practice of dental specialties, including oral medicine [ 10 ] oral and maxillofacial surgery [ 11 , 12 , 13 ], orthodontics [ 14 ] and endodontics [ 4 , 15 ].…”
Section: Introductionmentioning
confidence: 99%